The Cultural and Linguistic Diversity of 3-Year-Old Children with Hearing Loss - Crowe, Kathryn (Oxford University Press, 2012)
Understanding the cultural and linguistic diversity of young children with hearing loss informs the provision of assessment, habilitation, and education services to both children and their families. Data describing communication mode, oral language use, and demographic characteristics were collected for 406 children with hearing loss and their caregivers when children were 3 years old. The data were from the Longitudinal Outcomes of Children with Hearing Impairment (LOCHI) study, a prospective, population-based study of children with hearing loss in Australia. The majority of the 406 children used spoken English at home; however, 28 other languages also were spoken. Compared with their caregivers, the children in this study used fewer spoken languages and had higher rates of oral monolingualism. Few children used a spoken language other than English in their early education environment. One quarter of the children used sign to communicate at home and/or in their early education environment. No associations between caregiver hearing status and children’s communication mode were identified. This exploratory investigation of the communication modes and languages used by young children with hearing loss and their caregivers provides an initial examination of the cultural and linguistic diversity and heritage language attrition of this population. The findings of this study have implications for the development of resources and the provision of early education services to the families of children with hearing loss, especially where the caregivers use a language that is not the lingua franca of their country of residence.